HUBUNGAN PENGETAHUAN PEROKOK DENGAN DENTAL STAIN PADA MASYARAKAT DI GAMPONG LAM RAYA KABUPATEN ACEH BESAR - Mufizarni; Elfi Zahara (Journal Dental Health, 2022)
Smoking is a bad oral habit and can cause long-term damage to both the health of the body and the oral cavity. Smoking is one of the main causes of discoloration of teeth. This study aims to determine the relationship between the knowledge of smokers and dental stains in the people of Gampong Lamraya, Aceh Besar District in 2022. The population in this study is the people of Gampong Lam Raya, Aceh Besar District. Sampling using accidental sampling technique with inclusion criteria, namely the respondents are male, active smokers, aged 17-45 years, and willing to be invited to participate. The number of samples in the study was 30 respondents. The instruments used are diagnostic sets, KSP, and questionnaires. Data analysis using Chi-Square statistical test with 0.05. The results showed that the highest knowledge of smokers about dental stains was in the poor category, namely 21 respondents (70%) and 16 respondents (53.3%) having dental stains. The results of the Chi-Square statistic test obtained a P value of 0.000 with a value of 0.05 and df = 1, meaning that there is a relationship between knowledge of smokers and the presence of dental stains in the people of Gampong Lam Raya, Aceh Besar District. It is hoped that the community can reduce cigarette consumption because it can affect dental health (dental stain) and health in general.